Fertility and infant mortality trends in Nicaragua 1964-1993. The role of women's education - Pena, R. (BMJ Group, 1999)
OBJECTIVES: To assess trends in fertility and infant mortality rates (IMR) in Leon, Nicaragua, and to examine the effect of women's education on these trends during 1964-1993, a period of rapid social change. DESIGN: Cross sectional survey, based on random cluster sampling. A retrospective questionnaire on reproductive events was used. SETTING: The municipality of Leon, which is the second largest city in Nicaragua, with a total population of 195,000 inhabitants. SUBJECTS: 10,867 women aged 15-49 years, corresponding to 176,281 person years of reproductive life. Their children contributed 22,899 person years under 12 months of age to the IMR analysis. MAIN OUTCOME MEASURES: Fertility rate (number of pregnancies per 1000 person years) for specific age groups and calendar periods, total fertility rate, and IMR. RESULTS: Fertility rates and IMR declined in parallel, especially during the 1980s. However, education specific fertility rates did not decline, but the proportion of educated young women increased from 20% to 46%. This had also an impact on the overall IMR decline, although IMR reduction mainly took place among infants of women without formal education, decreasing from 118 to 69 per 1000 during the observation period. CONCLUSIONS: In this demographic transition over three decades, fertility and IMR declined simultaneously. The decreasing trend in fertility was mainly explained by an increase in women's education, while the IMR decline seemed to be the result of health interventions, specially targeted to poorer groups of women and their infants. Thus, social differences in fertility rates remained unchanged, while equity in chances of child survival increased.